Second order sliding mode control for direct drive positioning system - Chiew, Tsung Heng; Jamaludin, Zamberi; Bani Hashim, Ahmad Yusairi; Abdullah, Lokman; Rafan, Nur Aidawaty; Maharof, M (Universiti Malaysia Pahang, Malaysia, 2017)
Second order sliding mode control is known for the ability to suppress chattering effect, often being associated with the implementation of a traditional sliding mode controller. The purpose of this paper is to demonstrate and compare the ability of super twisting sliding mode control to suppress chattering as well as to improve tracking performances against the traditional sliding mode controller. Both controllers were designed, numerically analysed and experimentally validated on a second order single-input single output system direct drive single axis positioning table. A continuous Kalman-Bucy filter was applied to estimate the velocity signal to further improve the overall tracking performance. Results showed that super twisting sliding mode controller was able to successfully suppress chattering effect by smoothening the control input through integration action to form a continuous function, thus dampening the effect of high frequency switching. The effectiveness of this control algorithm would promote its application in real-time application as it provides better control performance as compared to the standard sliding mode controller